INFRARED SPECTRAL AND MAGNETIC PROPERTIES OF BASIC COPPER(II) NITRATE PRODUCED BY SLOW TITRATION METHOD - Padmaningrum, Regina Tutik; Louise, Isana Supiah Yosephine; Yunita, Isti; Sugiyarto, Kristian Handoyo (Malaysian Journal of Science, 2022)
The main purposes for this work are to formulate and characterize the infrared (IR) and magnetic moment of the compounds resulted from the slow titration of copper(II) nitrate with sodium hydroxide and in the reverse procedures in an aqueous solution. The titration is carried out with various concentrations and at a constant temperature, ⁓ 19 oC, and monitored using pH meter with the rate of the titration⁓ 1 mL per minute. The corresponding data of change in mole ratio of Cu2+/OH- against pH reveals that the end point of the titration occurs at pH about 8, leading to stoichiometry formula, 3Cu(NO3)2.5Cu(OH)2, but Cu(NO3)2.5Cu(OH)2 in the reverse procedure (OH-/Cu2+). The pale blue for the former but deep blue compounds were isolated and then characterized IR spectroscopy and magnetic moment. Both compounds containing nitrate ion are evident from the corresponding IR spectra, and their magnetic moment values which were found in the range of 1.7-1.9 BM, are to be normal for copper(II) salt corresponding to one unpaired electron in the electronic configuration.